Utilization of microfluidic V-junction device to prepare surface itraconazole adsorbed nanospheres - Kucuk, Israfil; Ahmad, Zeeshan; Edirisinghe, Mohan; Orlu-Gul, Mine (Elsevier Science Bv, 2014)
Itraconazole is widely used as an anti-fungal drug to treat infections. However, its poor aqueous solubility results in low bioavailability. The aim of the present study was to improve the drug release profile by preparing surface itraconazole adsorbed polymethylsilsesquioxane (PMSQ) nanospheres using a V-junction microfluidic (VJM) device. In order to generate nanospheres with rough surface, the process flow rate of perfluorohexane (PFH) was set between 50 and 300 mu l min(-1) while the flow rate of PMSQ and itraconazole solution were constant at 300 mu l min(-1). Variations in the PFH flow rate enable the controlled size generation of nanospheres. PMSQ nanospheres adsorbing itraconazole were characterized by SEM, FTIR and Zetasizer. The release of itraconazole from PMSQ nanosphere surface was measured using UV spectroscopy. Nanosphere formulations with a range of sphere size (120, 320 and 800 nm diameter) were generated and drug release was studied. 120 nm itraconazole coated PMSQ nanospheres were found to present highest drug encapsulation efficiency and 13% drug loading in a more reproducible manner compared to 320 nm and 800 nm sized nanosphere formulations. Moreover, 120 nm itraconazole coated PMSQ nanospheres (encapsulation efficiency: 88%) showed higher encapsulation efficiency compared to 320 nm (encapsulation efficiency: 74%) and 800 nm (encapsulation efficiency: 62%) sized nanosphere formulations. The itraconazole coated PMSQ nanospheres were prepared continuously at the rate of 2.6 x 10(6) per minute via VIM device. Overall the VJM device enabled the preparation of monodisperse surface itraconazole adsorbed nanospheres with controlled in vitro drug release profile. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: Surface drug adsorbed; Nanospheres; Drug delivery; Itraconazole; V-junction microfluidic device